Pengaruh Kondisi Sosial Dan Ekonomi Terhadap Aspirasi Kerja Tenaga Kerja Provinsi Bali Pasca Pandemi Covid-19 - Made Santana Putra Adiyadnya; Putu Ayu Meidha Suwandewi (Warmadewa Economic Development Journal (WEDJ), 2024)
Indonesia as a developing country has serious problems in economic development, namely related to the high level of open unemployment. The Covid-19 pandemic that occurred in 2019 had a significant impact on the level of open unemployment in all regions, including Bali Province which relies heavily on the tourism sector. The Covid-19 pandemic, which has been going on for quite a long time, has indirectly influenced the work aspirations of the workforce in their efforts to obtain work after completing their studies.The purpose of this research is to analyze and obtain empirical evidence of the influence of economic conditions, social conditions and educational competence simultaneously on the employment aspirations of Bali Province workers after the Covid-19 Pandemic as well as to analyze and obtain empirical evidence of the influence of economic conditions, social conditions and educational competence partially towards the work aspirations of the Bali Province workforce after the Covid-19 Pandemic.The results of this research are that economic conditions, social conditions and educational competencies simultaneously affect the work aspirations of the Bali Province workforce after the Covid-19 Pandemic. Another result is that economic conditions have no effect on the work aspirations of Bali Province workers after the Covid-19 Pandemic, and social conditions and educational competencies partially have a positive and significant effect on the work aspirations of Bali Province workers after the Covid-19 Pandemi.